Teacher education for inclusion: personal, professional and academic histories - Versoza-Carvalhal, Cassiana Stersa; de Melo, Camila Muchon; da Silva, Silvia Aparecida Fornazari (Perspectivas em Análise do Comportamento, 2017)
The goal of this study was to analyze the content of the verbal report of teachers who work with students included in order to investigate the importance of personal history, the history of professional and academic background to the development of favorable behaviors or not inclusion. An interview was conducted with eight teachers in the regular education of Londrina who had included students in their classrooms. Were investigated aspects of their personal, professional and academic training related to special education inclusive, as well as its expertise and opinion in the inclusion. e most relevant aspects for the proper preparation of teachers to work with inclusive education were the professional experience of practical experience in special education.